2012
DOI: 10.1051/0004-6361/201219225
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Herbig Ae/Be stars withHerschel/PACS

Abstract: We observed a sample of 20 representative Herbig Ae/Be stars and 5 A-type debris discs with PACS onboard Herschel, as part of the GAS in Protoplanetary Systems (GASPS) project. The observations were done in spectroscopic mode, and cover the far-infrared line is only detected in 25% and CO J = 18-17 in 45% (and fewer cases for higher J transitions) of the Herbig Ae/Be stars, while for [C ii] 157 μm, we often find spatially variable background contamination. We show the first detection of water in a Herbig Ae di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
190
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(205 citation statements)
references
References 118 publications
(105 reference statements)
13
190
2
Order By: Relevance
“…Kamp & van Zadelhoff (2001) predict [O I] and [C II] play a large role in gas cooling, while Thi et al (2014), in their modeling of the HD 141569 system, find that CO itself can play a major role. Strong far-infrared emission from [O I] and [C II], at levels more comparable to protoplanetary disks than to debris disks, has been measured from the disk around HD 141569 (Meeus et al 2012) although these lines may only contribute significantly to the upper low density regions of the disk rather than the midplane being traced by our CO observations. Two-dimensional photodissociation region models (e.g., Hollenbach & Tielens 1999) predict that at the densities where CO becomes the dominant coolant, but before collisional equilibrium with the dust sets in, the gas temperature can drop below that of the dust.…”
Section: Discussionmentioning
confidence: 64%
“…Kamp & van Zadelhoff (2001) predict [O I] and [C II] play a large role in gas cooling, while Thi et al (2014), in their modeling of the HD 141569 system, find that CO itself can play a major role. Strong far-infrared emission from [O I] and [C II], at levels more comparable to protoplanetary disks than to debris disks, has been measured from the disk around HD 141569 (Meeus et al 2012) although these lines may only contribute significantly to the upper low density regions of the disk rather than the midplane being traced by our CO observations. Two-dimensional photodissociation region models (e.g., Hollenbach & Tielens 1999) predict that at the densities where CO becomes the dominant coolant, but before collisional equilibrium with the dust sets in, the gas temperature can drop below that of the dust.…”
Section: Discussionmentioning
confidence: 64%
“…These differences are likely due to different excitation mechanisms (e.g. collisions, infrared pumping, shocks) and different physical conditions (temperature and column density (Fedele et al 2012;Meeus et al 2012) and have been confirmed through a stacking analysis. Two other Herbig AeBe stars show hints of H 2 O emission: HD 142527 and HD 104237.…”
Section: H 2 Omentioning
confidence: 67%
“…The difference between the mid-and far-IR ratios are not significant. Herbig AeBe: the major difference between short and long wavelengths is the lack of any H 2 O lines at near-IR (Mandell et al 2008;Fedele et al 2011) whereas weak H 2 O lines are detected at mid-and far-IR in some sources (Pontoppidan et al 2010;Fedele et al 2012;Meeus et al 2012). Even though the detection rate of warm H 2 O is low and the individual lines are weak (< a few 10 −17 W m −2 ), this finding suggests a different H 2 O abundance between the inner and outer disk.…”
Section: Comparison To Near-and Mid-ir Spectroscopymentioning
confidence: 99%
“…The far-IR lines of CO in HAEBEs and TTS were also observed by DIGIT (Sturm et al 2010) and GASPS (Meeus et al 2012) with the instrument PACS (Poglitsch et al 2010) onboard Herschel (Pilbratt et al 2010). Bruderer et al (2012;hereafter BR12) have modelled pure rotational CO transitions in HD 100546 (Sturm et al 2010).…”
Section: Introductionmentioning
confidence: 90%
“…The HAEBE stars with strong L UV and flaring discs (group I) often have a high [O ] 63 µm line flux (Meeus et al 2012; Table 2. Observed CO line fluxes in W m −2 × 10 −18 (first row) and adjacent continuum flux density in Jy (second row).…”
Section: Relation With the (Uv) Luminositymentioning
confidence: 99%